Collision of the mocha fracture zone and a <4 Ma old wave of orogenic uplift in the Andes (36°-38°S) - Folguera Telichevsky, Andres (2009)
The southern Central and northern Patagonian Andes (34°-45°S) are characterized by low to no crustal seismicity at the retroarc fold and thrust belt, in contrast to the Pampean flat subduction zone located immediately to the north (27°-33°30'S). Detailed examination of this area shows no indication of contractional neotectonics with the exception of the segment located between 36° and 38°S. There, out-of-sequence transpressional deformation, initially developed in the 1.7-1.4 Ma interval, affects the western retroarc between 36° and 38°S next to the arc zone. It is between these latitudes that contractional deformation <3.6 Ma old developed in the forearc region. Oblique collision of the Mocha fracture zone and its associated rise explains the distribution, extent, and timing of <3.6 Ma contractional deformations from the forearc to the foreland, as well as incipient shallowing of the Nazca plate beneath the South American plate, which has been inferred from seismic, gravimetric, and arc dynamics studies.